Religious Education and Islamic Religious Education in Europe Reflections for Ireland - Sai, Youcef (Graduate Students’ Union of the University of Dublin, Trinity College, 2015)
Debate about the place of religion in public education, both in Europe and worldwide, has increased in the twenty-first century. The role of faith-based schools in secular societies and the need for provision of religious education [RE] have increasingly become topics of controversy. In Europe, RE is a multi-layered term meaning different things in different contexts. Some have argued for its continued provision, while others have contested the need for it in an age that could seem increasingly ‘postreligious’. This paper examines various forms of RE and explores some arguments that might support its retention and call for its abolition in Europe with a particular focus on Ireland. The so-called rise of Islamophobia, in particular, makes these questions more acute. Therefore, after an initial exploration of background debates on RE and faith-based schooling, I introduce issues concerning the specific context and forms of principles in debates on Islamic religious education [IRE] in various European countries. Empirical research on Islamic education in Ireland is currently very limited, thus (in order to add to the theoretical discussion and understanding of how Islamic religious knowledge is formulated) the paper draws and extrapolates on existing ethnographic research conducted on how Islam is taught in public schools, similar in context to Ireland, elsewhere in Europe. The overall aim is to make a tentative attempt at contributing to our understanding of current debate on the legitimacy of IRE in pluralist societies (understood to mean those that advocate values such as personal autonomy, tolerance, diversity, critical openness and rational morality).
Keywords: Religious Education